Influence of cloudiness on erythemal solar irradiance in Marsaxlokk, Malta: Two case studies. (15th October 2016) - Bilbao, J.; Mateos, D.; Yousif, C.; Román, R.; De Miguel, A.
Highlights: Erythemal ultraviolet, global and diffuse irradiance measurements. Dependence of erythemal irradiance and cloud modification factor on clouds. Cloud cover and cloud modification factor relationships. Cloud optical thickness impact on erythemal, global and diffuse solar irradiance. Abstract: The effects of cloudiness on solar ultraviolet irradiance recorded between May and October 2012 at Marsaxlokk, Malta, are analysed. A statistical analysis of cloudiness is carried out, with clear skies (0–2 oktas) proving to be the most frequent conditions under total and low cloud cover. Hence, the dependence of erythemal UV solar irradiance (UVER) on total and low cloud cover is evaluated. In all cases, low clouds show higher attenuation. The effects of total cloud cover and low clouds on UVER are evaluated by means of the cloud modification factor (CMF) that is defined as the ratio between the measured irradiance and the estimated irradiance under cloud-free conditions. The results show that the effect on UVER is less than on global solar irradiance and that UVER transmissivity under overcast conditions can reach 50%. The effect of cloud optical thickness (COT) on UVER under all conditions shows a clear exponential dependence. The analysis shows that for fairly thick clouds with a COT of 10, the UVER reaching the Earth's surface is about 50% of its cloud-free value. The CMFUVER is found to decrease from 0.7 for COT = 0.5 to 0.25 for COT = 30. 10-min estimated COT from global solar irradiance are then compared with the GOME2 instrument. The correlation is found to be low. The influence of COT is studied by observing the evolution of irradiance on two cloudy days. When comparing the 10-min CMF under high COT for UVER and global irradiance, the first variable is found to be slightly higher than the second. As a consequence, changes in the ultraviolet index (UVI) due to COT effects are then described. Finally, the results obtained are compared with those from previous studies performed by different authors.